Comparison of structural characteristics and bioactivity of Tricholoma mongolicum Imai polysaccharides from five extraction methods - Zhang, Nan; Yang, Bing; Mao, Kemin; Liu, Yuwei; Chitrakar, Bimal; Wang, Xianghong; Sang, Yaxin (Frontiers in Nutrition, 2022)
Tricholoma mongolicum Imai is an edible fungus rich in various health-promoting compounds, such as polysaccharides, polypeptides, polyunsaturated fatty acids, etc., and among them, polysaccharides have gotten more attention in recent research trends. This study explored the extraction of polysaccharides from T. mongolicum Imai by five extraction methods, including hot water extraction, ultrasound extraction, enzyme-assisted extraction, 0.1 M HCL extraction, and 0.1 M NaOH extraction. The effects of these extraction methods on the yield, chemical structure, apparent morphology, and the antioxidant activities of Tricholoma mongolicum Imai polysaccharides (TMIPs) were investigated in this study. The data showed that 0.1 M NaOH extraction produced the highest extraction yield compared to the other extraction methods. The results of high-performance gel permeation chromatography (HPGPC) and scanning electron microscopy (SEM) showed that different extraction methods had significant effects on the molecular weight and morphology of TMIPs. The results of Fourier transform infrared (FT-IR), X-ray diffraction (XRD), and thermogravimetric analysis showed that the extraction methods had no significant difference in functional groups, crystal structure, and thermal stability of TMIPs. The antioxidant activity of TMIPs extracted by ultrasound extraction was more prominent among the five polysaccharides, which might be related to a large number of low-molecular-weight components in molecular weight distribution.